Physicians' experiences with pharmacists as new members of the interprofessional emergency department team. A qualitative study. - Tine Johnsgård; Renate Elenjord; Birgitte Zahl-Holmstad; Kristian Svendsen; Elin C Lehnbom; Eirik H Ofstad; Torsten Risør; Beate H Garcia (PLoS ONE)
Pharmacists in emergency departments (EDs) can alleviate physicians' workload by handling medication-related tasks and offer valuable contributions in interprofessional teams. We aimed to explore physicians' experiences working with pharmacists in EDs, and their perspectives on future permanent collaboration. We conducted semi-structured interviews with twenty physicians from two EDs and analyzed the data using thematic analysis. Four main themes emerged, comprising twelve subthemes that highlighted both challenges and motivations. Theme 1: time addressed physicians' time constraints, and the potential for time reallocation with assistance from pharmacists. Theme 2: various roles of pharmacists focused on the diverse roles of pharmacists who supported patient care and junior physicians, but faced challenges like availability and space constraints. Theme 3: teamwork concerned how pharmacists were trusted, brought valuable insights, and enhanced patient safety, yet there were ambiguous views on responsibility and cultural differences. Theme 4: future perspectives focused on how physicians favored a permanent inclusion of pharmacists in the ED, suggesting that they could independently conduct MedRec. Our findings suggest that pharmacists should be permanently integrated in ED teams. However, there is a need to address challenges related to space and legal regulations to enhance interprofessional collaboration.